K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

3 tháng 11 2024

8x3 - 36x2 + 54x - 26 = 0

8x3 - 8x2 - 28x2 + 28x + 26x - 26 = 0

8x2(x - 1) - 28x(x - 1) + 26(x - 1) = 0

(x - 1)(8x2 - 28x + 26) = 0

x - 1 = 0 hoặc 8x2 - 28x + 26 = 0

TH1: x - 1 = 0 

         x      =  1

TH2: 8x2 - 28x + 26 = 0 (vô nghiệm)

Vậy x = 1

18 tháng 4 2018

Ta có 8 x 3   +   36 x 2   +   54 x   +   27   =   ( 2 x ) 3   +   3 ( 2 x ) 2 . 3   +   3 . 2 x . 3 2   +   3 3   =   ( 2 x   +   3 ) 3

 

Đáp án cần chọn là: B

13 tháng 6 2021

`a)(x-6)^2-(x+6)^2=12`

`<=>(x-6-x-6)(x-6+x+6)=12`

`<=>-12.2x=12`

`<=>2x=-1`

`<=>x=-1/2`

Vậy `x=-1/2`

`b)36x^2-12x+1=81`

`<=>(6x-1)^2=81`

`<=>(6x-1-9)(6x-1+9)=0`

`<=>(6x-10)(6x+8)=0`

`<=>(3x-5)(3x+4)=0`

`<=>` \(\left[ \begin{array}{l}x=\dfrac53\\x=-\dfrac43\end{array} \right.\) 

`c)x^2-4x-12=0`

`<=>x^2-6x+2x-12=0`

`<=>x(x-6)+2(x-6)=0`

`<=>(x-6)(x+2)=0`

`<=>` \(\left[ \begin{array}{l}x=-2\\x=6\end{array} \right.\) 

`d)x^2-5x-6=0`

`<=>x^2-6x+x-6=0`

`<=>x(x-6)+x-6=0`

`<=>(x-6)(x+1)=0`

`<=>` \(\left[ \begin{array}{l}x=6\\x=-1\end{array} \right.\) 

7 tháng 11 2021

\(a,\Leftrightarrow6x-9+4-2x=-3\Leftrightarrow4x=2\Leftrightarrow x=\dfrac{1}{2}\\ b,\Leftrightarrow\left(x-2021\right)\left(x-6\right)=0\Leftrightarrow\left[{}\begin{matrix}x=2021\\x=6\end{matrix}\right.\\ c,\Leftrightarrow\left(2x-3-6x\right)\left(2x-3+6x\right)=0\\ \Leftrightarrow\left[{}\begin{matrix}-3-4x=0\\8x-3=0\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=-\dfrac{3}{4}\\x=\dfrac{3}{8}\end{matrix}\right.\)

Bài 2: 

a: \(A=\left[a+\left(b-c\right)\right]^2+\left[a-\left(b-c\right)\right]^2\)

\(=a^2+2a\left(b-c\right)+\left(b-c\right)^2+a^2-2a\left(b-c\right)+\left(b-c\right)^2\)

\(=2a^2+2\left(b-c\right)^2\)

\(=2\cdot1^2+2\left(3+1\right)^2=2+32=34\)

b: \(B=a^2+2ab+b^2-a^2+2ab-b^2=4ab=4\cdot2\cdot5=40\)

Bài 2:

b: \(=\left(x^2+x+4+3x\right)\left(x^2+x+4+5x\right)\)

\(=\left(x^2+4x+4\right)\left(x^2+6x+4\right)\)

\(=\left(x+2\right)^2\cdot\left(x^2+6x+4\right)\)

c: \(=25x^2-49y^2-\left(5x+7y\right)\)

=(5x+7y)(5x-7y-1)

d: \(8x^3-36x^2+54x-27=\left(2x-3\right)^3\)

`@` `\text {Ans}`

`\downarrow`

`a,`

`(2x - 1)^2 - 25 = 0`

`<=> (2x - 1)^2 = 25`

`<=> (2x - 1)^2 = (+-5)^2`

`<=>`\(\left[{}\begin{matrix}2x-1=5\\2x-1=-5\end{matrix}\right.\)

`<=>`\(\left[{}\begin{matrix}2x=6\\2x=-4\end{matrix}\right.\)

`<=>`\(\left[{}\begin{matrix}x=3\\x=-2\end{matrix}\right.\)

Vậy, `S = {-2; 3}`

`b,`

`8x^3 - 50x = 0`

`<=> x(8x^2 - 50) = 0`

`<=>`\(\left[{}\begin{matrix}x=0\\8x^2-50=0\end{matrix}\right.\)

`<=>`\(\left[{}\begin{matrix}x=0\\8x^2=50\end{matrix}\right.\)

`<=>`\(\left[{}\begin{matrix}x=0\\x^2=\dfrac{25}{4}\end{matrix}\right.\)

`<=>`\(\left[{}\begin{matrix}x=0\\x=\pm\dfrac{5}{2}\end{matrix}\right.\)

Vậy, `S = {-5/2; 0; 5/2}.`

17 tháng 7 2023

a) (2x - 1)² - 25 = 0

(2x - 1)² - 5² = 0

(2x - 1 - 5)(2x - 1 + 5) = 0

(2x - 6)(2x + 4) = 0

2x - 6 = 0 hoặc 2x + 4 = 0

*) 2x - 6 = 0

2x = 6

x = 3

*) 2x + 4 = 0

2x = -4

x = -2

Vậy x = -2; x = 3

b) 8x³ - 50x = 0

2x(4x² - 25) = 0

2x[(2x)² - 5²] = 0

2x(2x - 5)(2x + 5) = 0

2x = 0 hoặc 2x - 5 = 0 hoặc 2x + 5 = 0

*) 2x = 0

x = 0

*) 2x - 5 = 0

2x = 5

x = 5/2

*) 2x + 5 = 0

2x = -5

x = -5/2

Vậy x = -5/2; x = 0; x = 5/2

28 tháng 10 2021

8x3-50x=0
x(8x2-50)=0
TH1: x=0           TH2: 8x2-50=0
                                   8x2     = 50
                                     x2     = \(\dfrac{25}{4}\)
                                     x       = + - \(\dfrac{5}{2}\)
vậy x\(\in\){0,+-\(\dfrac{5}{2}\)}

28 tháng 10 2021

em cảm ơn ạ

Bài 1: 

a: \(8x^3-2x=2x\left(4x^2-1\right)=2x\left(2x-1\right)\left(2x+1\right)\)

c: \(-5m^3\left(m+1\right)+m+1=\left(m+1\right)\left(-5m^3+1\right)\)

 

a: Ta có: \(2\left(x-2\right)^3=2-x\)

\(\Leftrightarrow2\left(x-2\right)^3+x-2=0\)

\(\Leftrightarrow x-2=0\)

hay x=2

b: ta có: \(8x^3-72x=0\)

\(\Leftrightarrow x\left(x-3\right)\left(x+3\right)=0\)

\(\Leftrightarrow\left[{}\begin{matrix}x=0\\x=3\\x=-3\end{matrix}\right.\)

c: Ta có: \(2x^3+3x^2+2x+3=0\)

\(\Leftrightarrow2x+3=0\)

hay \(x=-\dfrac{3}{2}\)